(untitled) (Quinto Sol, 2025)
This article aims to offer an overview of the development of Kirchnerism in the province of Córdoba. More specifically, we will focus on the selection and actions of its candidates during the 2005-2007 period. We will concentrate on the strategies deployed by the national executive branch to position this political force in the province. This analysis is guided by a methodology that involves a deep description, although combined with some theoretical tools linked to the coexistence between national and local politics. We will present, chronologically, those "chosen" by the national government to play leading roles in the province and attempt to explain the results of these selections and strategies.